Purchase Decisions for Users of Scarlett Whitening Products Viewed from Brand Ambassador, Product Innovation, and Word of Mouth: - Kusumawati, Laili Qodri; Istiatin, Istiatin; Damayanti, Ratna (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The purpose of this study is to understand how brand ambassadors, product innovation, and word-of-mouth influence how Scarlett Whitening is used in the Universitas Islam Batik Surakarta community of master's students. The methodology being used is a quantitative methodology. Around 1814 were surveyed, around 182 participated in the sample, and the sampling technique used purposive sampling. Utilized data include preliminary and secondary data obtained by observation, documentation, questionnaires, interviews, and literary studies. Data analysis techniques used in this study include the classic assumptions of normality, multicollinearity, and heteroskedasticity, regression line analysis, simultaneous and parsial analysis, and coefficient determination (R2). The findings of this study indicate that word of mouth advertising, product innovation, and brand ambassadorship have a positive and significant impact on customer perception. Keywords: Purchase Decision, Brand Ambassador, Product Innovation and Word Of Mouth